Abundant oleoyl-lysophosphatidylethanolamine in brain stimulates neurite outgrowth and protects against glutamate toxicity in cultured cortical neurons. (5th April 2021) - Hisano, Kazutoshi; Yoshida, Hironori; Kawase, Shiori; Mimura, Tetsuhiko; Haniu, Hisao; Tsukahara, Tamotsu; Kurihara, Taiga; Matsuda, Yoshikazu; Saito, Naoto; Uemura, Takeshi
Abstract: Lysophosphatidylethanolamines (LPEs) are bioactive lysophospholipids that have been suggested to play important roles in several biological processes. We performed a quantitative analysis of LPE species and showed their composition in mouse brain. We examined the roles of oleoyl-LPE (18:1 LPE), which is one of the abundant LPE species in brain. In cultured cortical neurons, application of 18:1 LPE-stimulated neurite outgrowth. The effect of 18:1 LPE on neurite outgrowth was inhibited by Gq/11 inhibitor YM-254890, phospholipase C (PLC) inhibitor U73122, protein kinase C (PKC) inhibitor Go6983 or mitogen-activated protein kinase (MAPK) inhibitor U0126. Additionally, 18:1 LPE increased the phosphorylation of MAPK/extracellular signal-regulated kinase 1/2. These results suggest that the action of 18:1 LPE on neurite outgrowth is mediated by the Gq/11/PLC/PKC/MAPK pathway. Moreover, we found that application of 18:1 LPE protects neurons from glutamate-induced excitotoxicity. This effect of 18:1 LPE was suppressed by PKC inhibitor Go6983. These results suggest that 18:1 LPE protects neurons from glutamate toxicity via PKC inhibitor Go6983-sensitive PKC subtype. Collectively, our results demonstrated that 18:1 LPE stimulates neurite outgrowth and protects against glutamate toxicity in cultured cortical neurons. Our findings provide insights into the physiological or pathological roles of 18:1 LPE in the brain. Graphical Abstract: